Feeding management of dairy calves / Manejo alimentar de bezerras leiteiras - Sílvio Romero Bulhões Azevedo; José Crisólogo de Sales Silva; Cristina Cavalcante Félix Bulhões Azevedo; Marília Ferro Marques Cavalcante; Cristian Cavalcante Félix da Silva (Universidade Estadual de Alagoas, 2016)
The objective of this review approaching aspects of nutrition of dairy calves, from birth to weaning, based on recent research. One of the main stages of cattle production is the creation of heifers, because this stage is defined the quality of animals that will make the squad. This kind of animal does not generate immediate income to the producer and because of this it does not receive due attention. The inadequate development caused by nutritional deficiencies may cause elevation of age at first childbirth, contributing to lower performance indexes and increasing production costs. Proper feed management of calves is an essential factor in ensuring the proper development of animals and a consequent good productivity of the farm. Therefore, the provision of colostrum, substitute in quality or milk and concentrate is essential for these animals to be weaned healthily, as soon as possible.